2020
DOI: 10.1017/s1062798720000964
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Secondary and Higher STEM Education – the Case of STEM@school

Abstract: Our rapidly changing society needs highly-qualified STEM professionals (experts in science, technology, engineering, and mathematics) to develop solutions to the problems it is facing. Many of the students who graduate from a STEM programme in secondary education, however, opt out of STEM when enrolling in higher education, often due to a loss of interest. To ensure sufficiently high and qualified enrolment in higher STEM education, we need to bridge this gap between secondary and higher STEM education by show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Thibaut et al (2018) identified in their review of literature the following five categories of instructional elements essential for teaching integrated STEM: (1) the explicit assimilation of learning goals, content and practices from different STEM disciplines; (2) a problem-centered learning environment that involves students in authentic, open-ended, ill-structured, realworld problems; (3) an inquiry-based learning environment that engages students in questioning, experimental learning and hands-on activities; (4) design-based learning that uses open-ended, hands-on design challenges; and (5) cooperative learning where students get the opportunity to communicate and collaborate with each other. This supports the claim that iSTEM conceptually differs from its separate subdisciplines and requires a unique pedagogical approach (De Meester et al, 2020;Roehrig et al, 2021). Therefore, this study focuses on motivation profiles in iSTEM courses.…”
Section: Integrated Stemsupporting
confidence: 73%
See 1 more Smart Citation
“…Thibaut et al (2018) identified in their review of literature the following five categories of instructional elements essential for teaching integrated STEM: (1) the explicit assimilation of learning goals, content and practices from different STEM disciplines; (2) a problem-centered learning environment that involves students in authentic, open-ended, ill-structured, realworld problems; (3) an inquiry-based learning environment that engages students in questioning, experimental learning and hands-on activities; (4) design-based learning that uses open-ended, hands-on design challenges; and (5) cooperative learning where students get the opportunity to communicate and collaborate with each other. This supports the claim that iSTEM conceptually differs from its separate subdisciplines and requires a unique pedagogical approach (De Meester et al, 2020;Roehrig et al, 2021). Therefore, this study focuses on motivation profiles in iSTEM courses.…”
Section: Integrated Stemsupporting
confidence: 73%
“…We previously established the importance of the quality of motivation (Vansteenkiste et al, 2009) and observed gender differences in both STEM interest and self-efficacy (Eccles, 2011;Ertl et al, 2017;Tzu-Ling, 2019). As iSTEM differs from 'segregated' STEM and requires a unique pedagogical approach (De Meester et al, 2020;Roehrig et al, 2021), more knowledge on motivation profiles towards iSTEM is needed. To better understand how motivation profiles in iSTEM relate to STEM test scores and to identify possible gender differences, the following three research questions were developed to guide this study:…”
Section: Goals Of This Studymentioning
confidence: 99%
“…To endorse the value of longlasting (educational) research in each of the different STEM disciplines (NRC, 2012), we add the extra principle of research-based learning. As a result, we advocate the five key principles for establishing high-quality iSTEM education in secondary school classrooms shown at the left of Figure 1 (De Meester et al, 2020). Based on the research literature on instructional design for integrated STEM education (NAE et al, 2014;Felder et al, 2016), we translated these five key principles into 10 requirements for high-quality iSTEM education, shown at the right of Figure 1.…”
Section: Theoretical Framework Istem Key Principles and Requirementsmentioning
confidence: 99%
“…With these aspirations for secondary STEM education, the 4-year research project STEM@school was launched in Flanders (Belgium) in 2014 (De Meester et al, 2020). STEM@school engaged 30 teams of STEM teachers to implement iSTEM learning materials in their classroom, 10 of which were also involved as teacher design teams (TDTs) in the design of these learning materials.…”
Section: Introductionmentioning
confidence: 99%
“…At societal level it will help to cater for sufficient, well-educated practitioners in these areas (Bybee, 2013). Hence there is a compelling need for appropriate Science, Technology, Engineering, and Mathematics (STEM) education, even at secondary school level (De Meester et al, 2020).…”
Section: Introductionmentioning
confidence: 99%